Simultaneous multislice imaging for native myocardial T1 mapping: improved spatial coverage in a single breath-hold - Weingärtner, Sebastian (Magnetic resonance in medicine, 2017)
Purpose To develop a saturation recovery myocardial T1 mapping method for the simultaneous multislice acquisition of three slices. Methods Saturation pulse-prepared heart rate independent inversion recovery (SAPPHIRE) T1 mapping was implemented with simultaneous multislice imaging using FLASH readouts for faster coverage of the myocardium. Controlled aliasing in parallel imaging (CAIPI) was used to achieve minimal noise amplification in three slices. Multiband reconstruction was performed using three linear reconstruction methods: Slice- and in-plane GRAPPA, CG-SENSE, and Tikhonov-regularized CG-SENSE. Accuracy, spatial variability, and interslice leakage were compared with single-band T1 mapping in a phantom and in six healthy subjects. Results Multiband phantom T1 times showed good agreement with single-band T1 mapping for all three reconstruction methods (normalized root mean square error <1.0%). The increase in spatial variability compared with single-band imaging was lowest for GRAPPA (1.29-fold), with higher penalties for Tikhonov-regularized CG-SENSE (1.47-fold) and CG-SENSE (1.52-fold). In vivo multiband T1 times showed no significant difference compared with single-band (T1 time ± intersegmental variability: single-band, 1580 ± 119 ms; GRAPPA, 1572 ± 145 ms; CG-SENSE, 1579 ± 159 ms; Tikhonov, 1586 ± 150 ms [analysis of variance; P = 0.86]). Interslice leakage was smallest for GRAPPA (5.4%) and higher for CG-SENSE (6.2%) and Tikhonov-regularized CG-SENSE (7.9%). Conclusion Multiband accelerated myocardial T1 mapping demonstrated the potential for single-breath-hold T1 quantification in 16 American Heart Association segments over three slices. A 1.2- to 1.4-fold higher in vivo spatial variability was observed, where GRAPPA-based reconstruction showed the highest homogeneity and the least interslice leakage.